2017
DOI: 10.18805/ijar.b-3276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of acid ensiled fish waste on production performance, egg quality and serum biochemistry in layer Japanese quail (Coturnix coturnix japonica)

Abstract: Five weeks old layer Japanese quail (Coturnix coturnix japonica) birds (180 nos) were randomly distributed into 4 dietary groups with 3 replicates each for 98 days to study the effect of dietary inclusion of acid ensiled fish waste silage on the production performance, egg quality, feed cost, and serum biochemical profile. Fish meal in control diet was replaced by supplementing fish silage at 3%, 6% and 12% of the diet. Significant increase in egg production (p<0.05) and the lowest feed conversion ratio were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Optimized utilization of CPL and FFW presents an economically viable strategy for boosting yields and profitability compared to conventional diets alone. This finding aligns with similar improvements reported in profitability metrics associated with CPL by Ezenwosu et al [20] and Unigwe et al [3], as well as with FFW by Garcés et al [9], Shabani et al [16], and Tanuja et al [27]. However, contrasting results were observed by Sari et al [4] and Banjoko et al [6], who found no direct profitability impacts from CPL.…”
Section: Economic Profitabilitysupporting
confidence: 89%
“…Optimized utilization of CPL and FFW presents an economically viable strategy for boosting yields and profitability compared to conventional diets alone. This finding aligns with similar improvements reported in profitability metrics associated with CPL by Ezenwosu et al [20] and Unigwe et al [3], as well as with FFW by Garcés et al [9], Shabani et al [16], and Tanuja et al [27]. However, contrasting results were observed by Sari et al [4] and Banjoko et al [6], who found no direct profitability impacts from CPL.…”
Section: Economic Profitabilitysupporting
confidence: 89%
“…Similar observations were recorded by Salah et al (2014), who reported a significant (P0.05) increase in total protein and albumin levels in common carp, Cyprinus carpio where FM was replaced with fish bio silage at different levels (0, 25, 50 or 75%). The concentration of serum biochemical constituents (total protein, albumen, globulin, cholesterol, triglyceride, alkaline phosphatase, urea and creatinine concentration) did not vary significantly with dietary inclusion of acid ensiled fish waste silage @ 3,6 and 12% by replacing FM in Japanese quail (Tanuja et al, 2018). Lipid profile in terms of Cholesterol (mg dl -1 ) and Triglycerides (mg dl -1 ) showed an increase an all the experimental diets (Fig 3) as compared to control with highest values in D3 (366.53 and 56.00) and lowest in D1 (16.00) and D6 (193.20) respectively.…”
Section: Biochemical Parameters and Lipid Profilementioning
confidence: 91%